Nilai-Nilai Pendidikan Agama Islam dalam Sholat Berjamaah - Muhtadi Muhtadi; Rizka Aminatul Maghfiroh (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2018)
This study aims to describe the values ​​of Islamic education and the values ​​of Islamic education in congregational prayer. This research is a type of library research (library research). The approach used is a historical approach. The analysis technique that I use in this study is an analysis of the literature that is relevant to the subject matter. This means that in writing this research report focuses on library materials by searching and reviewing academic standards of literature, then looking for explicit and implicit meanings. The results of the study state that the value of Islamic education is an abstract that is used as a guideline and general principles in acting and acting. The value of Islamic education meant is tauhid (faith), worship and morals. While the values ​​of Islamic education in congregational prayers are divided into two reviews. First, it is reviewed from the terms of the congregational prayer and from the review of the congregational prayers. From this review, the value of Islamic education contained in congregational prayers includes: the value of sincerity, gratitude, discipline, cleanliness, togetherness and praise.